2001
DOI: 10.1103/physrevlett.86.4394
|View full text |Cite
|
Sign up to set email alerts
|

Two-Stage Magnetization Reversal in Exchange Biased Bilayers

Abstract: MnF 2 ͞Fe bilayers exhibit asymmetric magnetization reversal that occurs by coherent rotation on one side of the loop and by nucleation and propagation of domain walls on the other side of the loop. Here, we show by polarized neutron reflectometry, magnetization, and magnetotransport measurements that for samples with good crystalline "quality" the rotation is a two-stage process, due to coherent rotation to a stable state perpendicular to the cooling field direction. The result is remarkably asymmetrically sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
86
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(92 citation statements)
references
References 30 publications
5
86
1
Order By: Relevance
“…This is in most cases contrary to the experimental observation of magnetic domains in such layers, 4 -6 although for some cases, a coherent magnetization rotation has been also reported. 7 Measurements of the exchange bias and coercive field as a function of the applied field angle 8,9 are very informative and provide a good test for the validity of existing theoretical models. 10 This article presents a study of the domain patterns during the magnetization reversal in exchange-biased Co/NiO bilayers, for different angles between the applied magnetic field and the exchange biasing axis.…”
mentioning
confidence: 99%
“…This is in most cases contrary to the experimental observation of magnetic domains in such layers, 4 -6 although for some cases, a coherent magnetization rotation has been also reported. 7 Measurements of the exchange bias and coercive field as a function of the applied field angle 8,9 are very informative and provide a good test for the validity of existing theoretical models. 10 This article presents a study of the domain patterns during the magnetization reversal in exchange-biased Co/NiO bilayers, for different angles between the applied magnetic field and the exchange biasing axis.…”
mentioning
confidence: 99%
“…The most prominent example of an asymmetric reversal occurs in Fe/ MnF 2 , which exhibits a pronounced step on only one side of the hysteresis loop. 3 Polarized neutron reflectometry ͑PNR͒ showed that this step is related to coherent rotation of the magnetization, 3,4 which is pinned in a potential minimum transverse to the applied magnetic field. As PNR is not sensitive to the direction of the transverse moment it cannot determine the chirality of the magnetization vector upon magnetization reversal.…”
mentioning
confidence: 99%
“…Details of the sample preparation and structural characterization are given elsewhere. 3 MOKE measurements were performed with an in-plane magnetic field H ext oriented horizontally ͓Fig. 1͑a͔͒ and at 45°with respect to the ͓001͔ direction of the AFM twins.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To date, neutron scattering has been used extensively to investigate exchange-biased systems. These measurements provide insight into the magnetization reversal processes of the ferromagnet [38,296] and the spin structure of the antiferromagnet [31,39,227]. Neutron diffraction has also been used to identify and characterize new antiferromagnetic materials, such as MnN [30,297] and MnPd [40] that may exhibit better performance in spin-valve structures.…”
Section: Magnetic Recording Heads Present and Future Directionsmentioning
confidence: 99%